2006
DOI: 10.1128/jvi.80.2.1015-1024.2006
|View full text |Cite
|
Sign up to set email alerts
|

Low pH-Dependent Endosomal Processing of the Incoming Parvovirus Minute Virus of Mice Virion Leads to Externalization of the VP1 N-Terminal Sequence (N-VP1), N-VP2 Cleavage, and Uncoating of the Full-Length Genome

Abstract: Minute virus of mice (MVM) enters the host cell via receptor-mediated endocytosis. Although endosomal processing is required, its role remains uncertain. In particular, the effect of low endosomal pH on capsid configuration and nuclear delivery of the viral genome is unclear. We have followed the progression and structural transitions of DNA full-virus capsids (FC) and empty capsids (EC) containing the VP1 and VP2 structural proteins and of VP2-only virus-like particles (VLP) during the endosomal trafficking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
118
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 56 publications
8
118
0
Order By: Relevance
“…Thus, acidification can be essential for viruses which internalize within CCVs (Damm & Pelkmans, 2006;Marsh & Helenius, 2006;Smith & Helenius, 2004). Studies of parvovirus entry reported that minute virus of mice, adeno-associated virus and CPV internalization require endosomal acidification, and the endosomal acidic environment may induce capsid conformational changes vital for viral release from endosomes to the cytoplasm (Basak & Compans, 1989;Douar et al, 2001;Mani et al, 2006). Blocking acidification of endosomes is a way of suggesting involvement of the clathrin system in cargo entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, acidification can be essential for viruses which internalize within CCVs (Damm & Pelkmans, 2006;Marsh & Helenius, 2006;Smith & Helenius, 2004). Studies of parvovirus entry reported that minute virus of mice, adeno-associated virus and CPV internalization require endosomal acidification, and the endosomal acidic environment may induce capsid conformational changes vital for viral release from endosomes to the cytoplasm (Basak & Compans, 1989;Douar et al, 2001;Mani et al, 2006). Blocking acidification of endosomes is a way of suggesting involvement of the clathrin system in cargo entry.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, reported studies have demonstrated that the clathrin-dependent endocytic pathway is the primary route for uptake for some members of the family Parvoviridae into cells (Douar et al, 2001;Mani et al, 2006;Ros et al, 2002;Vendeville et al, 2009). To determine BPV entry dependence on clathrin, CHPZ, a cationic amphiphilic drug that inhibits the formation of clathrin-coated pits at the plasma membrane was used.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively rapid endocytic uptake of parvoviruses appears to be followed by slower traffic along the endocytic compartments toward the nucleus. The endosomal pathway undertaken by parvoviruses appears to be complex and depends on the virus, its concentration, and likely the cell type (Dorsch et al, 2002;Mani et al, 2006;Sonntag et al, 2006;Suikkanen et al, 2003;Yuan & Parrish, 2001). Conformational alterations in capsid structure probably occur in the endosomal compartment facilitating uncoating and transport to the nucleus.…”
Section: Engulfmentmentioning
confidence: 99%
“…It has been widely used as a probe to study acid-mediated viral trafficking using a variety of virus models. Entry pathway studies of mouse polyomavirus (Liebl et al, 2006), feline calicivirus (Stuart & Brown, 2006), bovine viral diarrhea virus (Lecot et al, 2005), AAV (Bartlett et al, 2000), MVM (Mani et al, 2006;Ros et al, 2002), mouse hepatitis virus type 2 (Pu & Zhang, 2008), poliovirus , baculovirus (Long et al, 2006), hepatitis C virus (Blanchard et al, 2006), influenza virus (Guinea & Carrasco, 1995;Sieczkarski et al, 2003), HIV-1 (Fredericksen et al, 2002), and human rhinovirus 14 (Bayer et al, 1999) have analyzed the effects of Baf A1 on virus trafficking and examined the role of endosomal acidification in a route that leads to viral replication. For studies of parvovirus entry Baf A1 may be an inhibitor preferred over chlorpromazine because chlorpromazine is not only an inhibitor of clathrin lattice processing, but is also an inhibitor of phospholipase A2.…”
Section: Engulfmentmentioning
confidence: 99%
See 1 more Smart Citation